El botín y las culturas de la guerra en el espacio litoral rioplatense - Raúl Osvaldo Fradkin; Silvia Ratto (Amnis)
The aim of this article is to explore the practices and concepts that legitimized the right to the booty during the revolutionary wars in the Rio de la Plata. In the first revolutionary decade, very diverse actors – Creoles, Spanish, independent indigenous- participated in the revolutionary wars, in which they defined the identity of their enemies, forced the political alignment of the populations, supported their forces and channeled tensions between social and ethnic groups. This article is divided into two parts. The first section will analyze the forms that the struggle for the booty adopted within the regional hispano-creole society, and the second one will discuss the concepts the independent indigenous groups of the Chaco had about war and how these were reflected in their participation in the revolutionary wars.